2021
DOI: 10.4314/tjpr.v20i10.29
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different immunosuppressive drugs on the periodontal status and changes in periodontal pathogenic bacterial flora in rheumatoid arthritis patients

Abstract: Purpose: To investigate the prevalence of periodontal disease(s) and the associated bacteria among rheumatoid arthritis (RA) patients treated with different immunosuppressive drugs.Methods: Patients aged 18 – 65 years who had a 6-month history of RA, and were diagnosed as per the American College of Rheumatology and European League against Rheumatism, were included in the study. Supragingival plaque was removed by dentists. Using sterile paper strips, sub-gingival biofilm samples were collected from 5 of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Among the 35 included studies published until January 2023, 19 are cross‐sectional studies (Gamel et al., 2017; Hashimoto et al., 2021a, 2021b; Hatipoğlu et al., 2022; Jung et al., 2018; Kordtabar et al., 2019; Mayer et al., 2009, 2013; Mirrielees et al., 2010; Nik‐Azis et al., 2021; Ortiz et al., 2009; Pischon et al., 2008; Renvert et al., 2020; Romero‐Sanchez et al., 2017; Rovas et al., 2021; Schmalz et al., 2021; Wu et al., 2021; Yamashita et al., 2020; Ziebolz et al., 2018), 6 are case control studies (Äyräväinen et al., 2017, 2018a, 2018b; de Smit et al., 2021; Kobayashi et al., 2015; Kobayashi, Okada et al., 2014); 8 are longitudinal studies (Ancuta et al., 2017, 2020, 2021; Fabri et al., 2015; Kadkhoda et al., 2016; Kobayashi, Yokoyama et al., 2014; Savioli et al., 2012; Üstün et al., 2013), and 2 are cross‐sectional and longitudinal analyses in the one and the same article (Coat et al., 2015; Pers et al., 2008). All the studies were prospective except for one cross‐sectional study (Yamashita et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 35 included studies published until January 2023, 19 are cross‐sectional studies (Gamel et al., 2017; Hashimoto et al., 2021a, 2021b; Hatipoğlu et al., 2022; Jung et al., 2018; Kordtabar et al., 2019; Mayer et al., 2009, 2013; Mirrielees et al., 2010; Nik‐Azis et al., 2021; Ortiz et al., 2009; Pischon et al., 2008; Renvert et al., 2020; Romero‐Sanchez et al., 2017; Rovas et al., 2021; Schmalz et al., 2021; Wu et al., 2021; Yamashita et al., 2020; Ziebolz et al., 2018), 6 are case control studies (Äyräväinen et al., 2017, 2018a, 2018b; de Smit et al., 2021; Kobayashi et al., 2015; Kobayashi, Okada et al., 2014); 8 are longitudinal studies (Ancuta et al., 2017, 2020, 2021; Fabri et al., 2015; Kadkhoda et al., 2016; Kobayashi, Yokoyama et al., 2014; Savioli et al., 2012; Üstün et al., 2013), and 2 are cross‐sectional and longitudinal analyses in the one and the same article (Coat et al., 2015; Pers et al., 2008). All the studies were prospective except for one cross‐sectional study (Yamashita et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…NSAIDs and corticosteroids were used (alone or in combination) as primary treatment for RA in two cross‐sectional studies (Wu et al., 2021; Ziebolz et al., 2018). The authors found no intergroup differences in periodontal clinical parameters in term of PD, CAL, BOP, or PI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most RA patients need lifelong treatment, since RA has a long treatment cycle [6]. At present, the common RA treatment drugs are non-steroidal antiinflammatory drugs, slow-acting anti-rheumatic drugs and steroids, although their effects are not durable, while some result in adverse side effects [7]. Thus, it is important to find active and effective RA treatment drugs with few side effects.…”
Section: Introductionmentioning
confidence: 99%
“…The number of oral diseases has been on the increase, and this is closely related to poor living environments and unhealthy dietary habits. Meanwhile, with continuous improvement in people's living standards and their aesthetic requirements, more and more people prefer to go to hospitals to improve their aesthetics through oral prosthetics [2]. In oral prosthetics, the popular metal-ceramic restorations have the advantages of wear resistance, corrosion resistance, and high biocompatibility.…”
Section: Introductionmentioning
confidence: 99%